2010
DOI: 10.18632/aging.100218
|View full text |Cite
|
Sign up to set email alerts
|

CD36 plays an important role in the clearance of oxLDL and associated age-dependent sub-retinal deposits

Abstract: Age-related macular degeneration (AMD) represents the major cause of vision loss in industrialized nations. Laminar deposits in Bruch's membrane (BM) are among the first prominent histopathologic features, along with drusen formation, and have been found to contain oxidized lipids. Increases in concentrations of oxidized LDL (oxLDL) in plasma are observed with age and high fat high (HFHC) cholesterol diet. CD36 is the principal receptor implicated in uptake of oxLDL, and is expressed in the retinal pigment epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
67
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(71 citation statements)
references
References 42 publications
3
67
1
Order By: Relevance
“…Previously, oxLDL has been shown to stimulate extracellular matrix production. Because both LDL and oxLDL may contribute to the pathogenesis of AMD (29,30), we examined the degree to which LDL and oxLDL regulate RPE production and secretion of collagen IV, an extracellular matrix molecule found in sub-RPE deposits, through AhR (Fig. 8 D and E).…”
Section: Amd-like Rpe and Choroidal Pathology In Ahrmentioning
confidence: 99%
“…Previously, oxLDL has been shown to stimulate extracellular matrix production. Because both LDL and oxLDL may contribute to the pathogenesis of AMD (29,30), we examined the degree to which LDL and oxLDL regulate RPE production and secretion of collagen IV, an extracellular matrix molecule found in sub-RPE deposits, through AhR (Fig. 8 D and E).…”
Section: Amd-like Rpe and Choroidal Pathology In Ahrmentioning
confidence: 99%
“…While a number of sophisticated in vitro assays have been developed for assessing endothelial barrier function (Wegener & Seebach, 2014), we sought to assess a potentially more physiologically relevant model by analyzing mice with a conditional endothelial deletion of ATG7 (Torisu et al, 2013). We took advantage of the rich vascular plexus in the eye and the previously described transport of lipids from the choroidal blood vessels to the retinal pigment epithelium (RPE) (Picard et al, 2010). To assess whether the acute handling of modified lipids depends on intact endothelial autophagy, we injected control mice (WT/WT; VE-Cadherin Cre) or Atg7 endo mice (fl/fl;VE-Cadherin Cre) mice with fluorescently labeled OxLDL (dil-OxLDL).We next analyzed the retinas of mice 24 and 48 h after OxLDL injection by confocal microscopy.…”
mentioning
confidence: 99%
“…We also observed that the level of serum ox-LDL in premature CHD patients was higher than in controls. The main way to eliminate ox-LDL is phagocytosis of macrophages by SR, whose main member is CD36 (Park et al, 2012;Picard et al, 2010). So, the polymorphism of the CD36 gene could influence the level of ox-LDL.…”
Section: Discussionmentioning
confidence: 99%